The Application of Scrotoscope-Assisted Minimally Invasive Excision for Epididymal Mass: An Initial Report - Qin, Chuying; Yang, Jinrui; Zhang, Ruochen; Yang, Yaojin; Cai, Wanghai; Li, Tao; Zhu, Qingguo; Ye, Liefu; Gao, Yunliang; Wei, Yongbao (Frontiers in Surgery, 2022)
Background To compare the middle-term efficacy and safety results between scrotoscope-assisted (SA) minimally invasive excision and traditional open excision (OE) for the treatment of epididymal mass. Methods A total of 253 males with surgery excision of epididymal mass from 2012 to 2018 were included in this retrospective study. Patients were divided into two groups: the traditional OE group and the SA group. Patient demographics and intraoperative and postoperative outcomes were obtained and compared between these two groups. Results About 174 patients (68.8%) underwent SA, and the other 79 (31.2%) underwent OE. Demographic data were similar between the two groups. Compared with OE surgery, SA could significantly shorten the operating time (19.4 ± 4.1 vs. 53.8 ± 12.9 min), reduce blood loss (5.3 ± 1.5 vs. 21.3 ± 5.6 ml), and downsize the operative incision (1.5 ± 0.3 vs. 4.5 ± 0.8 cm). Additionally, postoperative complications were significantly less occurred in the SA group than those in OE (15.5% vs. 21.5%), in particular scrotal hematoma (1.7% vs. 12.7%) and incision discomfort (2.8% vs. 6.3%). Patients in the SA group had a significantly higher overall satisfaction score (94.8 ± 3.7 vs. 91.7 ± 4.9) and a significantly shorter length of hospital stay (4.1 ± 0.9 vs. 5.0 ± 1.5 days) than those in the OE group. No postoperative testicular atrophy occurred in the SA group. Conclusion SA is emerging as a novel and effective option with promising perspectives for epididymal mass therapy.